Inverse analysis for interface fracture toughness of Ti coating film by laser spallation method. (June 2018) - Arai, Masahiro; Sato, Yoshitaka; Sugiura, Daisuke; Nishimura, Masaomi; Ito, Hiroaki; Cho, Hideo
Highlights: 3D-elastic wave can be simulated using axi-symmetric boundary element analyses. Transfer functions were applied to compute dynamic stress intensity factor. Optimization was applied in the inverse analysis to stabilize the solution. Abstract: In the present paper, the interface fracture toughness between a Ti coating film and Al-alloy substrate is evaluated using a laser spallation method and a boundary element method. The fracture toughness can be estimated using inverse analyses by the boundary element method using a transfer function computed from the history of the displacement of the specimen. In the present study, an alternative boundary element program is developed for unsteady state vibration of an axi-symmetric solid body. The mode I interface fracture toughness between the Ti coating film and Al-alloy substrate is confirmed to be about 0.66 MPam 1/2 from the present investigation.